Osrednji literarni muzej kot pospeševalec literarnega turizma v Sloveniji - Zupan Sosič, Alojzija (Slavia Centralis, 2020)
Central literary museum as a promoter of literary tourism in SloveniaThe article delineates the arguments for the realization of the old idea of a central literary museum in Slovenia through three perspectives: national-affirmative, educational and touristic as well as the (new) seven-part typology. I advocate for the central literary museum as the seventh type i.e. a fusion of different types of museums elevating literal (cultural) tourism with its basic role – of a liaison – in the context of the four types of literary tourism and the Slovene and foreign tourist respective dispositions.
Keywords: central literary museum; Slovenia; literary tourism.